Latent Tuberculosis Infection Testing and Treatment at a Federally Qualified Health Center in Southern California: A Quality Improvement Project. Issue 2 (7th April 2022) - Truax, Fayette Nguyen; Low, Julie; Mochizuki, Tessa; Asfaha, Setie; Nguyen, Tu Ngoc; Carson, Michael; Katrak, Shereen; Shah, Neha; Nguyen, Duc
Abstract : Background: A key strategy to eliminate tuberculosis (TB) in the United States is to increase latent tuberculosis infection (LTBI) screening, testing, and treatment among non–US-born Asian populations. Purpose: The purpose was to increase LTBI screening, testing, and treatment at a community clinic. Methods: Retrospective baseline LTBI data were retrieved through electronic medical record review. Interventions included adoption of standardized TB risk assessment, training providers to use shorter LTBI treatment regimens, and use of a care coordinator. Chart abstraction to examine outcomes was conducted postintervention at 4 months. Results: In 2017, only 3 patients (7%) with LTBI were started on treatment. At 4 months postintervention, 28 (72%) patients with LTBI were started on treatment, of which 27 (96%) were placed on 3- to 4-month regimens. Conclusions: Training for providers and changes to clinic workflow, including use of a care coordinator, can help increase LTBI screening, testing, and treatment in community clinics.